Review of the design of power ultrasonic generator for piezoelectric transducer - Kuan Zhang; Guofu Gao; Chongyang Zhao; Yi Wang; Yan Wang; Jianfeng Li (Ultrasonics Sonochemistry, 2023)
The power ultrasonic generator (PUG) is the core device of power ultrasonic technology (PUT), and its performance determines the application of this technology in biomedicine, semiconductor, aerospace, and other fields. With the high demand for sensitive and accurate dynamic response in power ultrasonic applications, the design of PUG has become a hot topic in academic and industry. However, the previous reviews cannot be used as a universal technical manual for industrial applications. There are many technical difficulties in establishing a mature production system, which hinder the large-scale application of PUG for piezoelectric transducers. To enhance the performance of the dynamic matching and power control of PUG, the studies in various PUT applications have been reviewed in this article. Initially, the demand design covering the piezoelectric transducer application and parameter requirements for ultrasonic and electrical signals is overall summarized, and these parameter requirements have been recommended as the technical indicators of developing the new PUG. Then the factors affecting the power conversion circuit design are analyzed systematically to realize the foundational performance improvement of PUG. Furthermore, advantages and limitations of key control technologies have been summarized to provide some different ideas on how to realize automatic resonance tracking and adaptive power adjustment, and to optimize the power control and dynamic matching control. Finally, several research directions of PUG in the future have been prospected.